Exploring the Language of Conflict Rise and Conflict Resolution in Elechi Amadi’s The Great Ponds: A Systemic Functional Perspective - DATONDJI, COCOU ANDRÉ (My University, 2020)
This study investigates language use in an extract from The Great Ponds through the Transitivity analysis, within the lens of Halliday’s Systemic Functional Linguistics. The Transitivity analysis applied to a selected corpus from Elechi Amadi’s The Great Ponds shows the use of Material processes [95 (45%)], Mental processes [42 (20%)], Verbal processes [39 (18%)], Relational processes [30 (14%)] together with Existential and Behavioural processes in much lesser proportions. The mixed method analysis used in this paper served as a scientific ground to unveil and discuss the use of language to represent initiative takers, participants, circumstances of conflict rise and perpetuation. The work concluded on the major importance of language as a tool for peace construction and conflict resolution when used with care.
Keywords: Conflict; conflict rise; conflict resolution; leadership; interpersonal relations